2009
DOI: 10.1089/neu.2008.0835
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonyl Trifluoromethyl Ketone Is Neuroprotective after Spinal Cord Injury

Abstract: In spinal cord injury (SCI), neuronal and oligodendroglial loss occurs as a result of the initial trauma and the secondary damage that is triggered by excitotoxicity, free radicals, and inflammation. There is evidence that SCI ellicits increased cytosolic phospholipase A(2) (cPLA(2)) activity. The cleavage of phospholipids by cPLA(2) leads to release of fatty acids, and in particular arachidonic acid (AA), the metabolites of which have been associated with increased inflammation and oxidative stress. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…This construct was named as the PLA599 plasmid. Full-length cPLA 2 ␣ 3Ј-UTR was amplified using specific primers and cloned into plasmid pGL 3 promoter vector (Promega) using the XbaI and FseI sites. Various regions of the cPLA 2 ␣ 3Ј-UTR were amplified by PCR and cloned into pGEM-T easy vector (Promega) for in vitro transcription to synthesize probes used in RNA electrophoretic mobility shift assays (EMSAs) and biotin-labeled probe pulldown assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This construct was named as the PLA599 plasmid. Full-length cPLA 2 ␣ 3Ј-UTR was amplified using specific primers and cloned into plasmid pGL 3 promoter vector (Promega) using the XbaI and FseI sites. Various regions of the cPLA 2 ␣ 3Ј-UTR were amplified by PCR and cloned into pGEM-T easy vector (Promega) for in vitro transcription to synthesize probes used in RNA electrophoretic mobility shift assays (EMSAs) and biotin-labeled probe pulldown assays.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with the cPLA 2 ␣ inhibitor arachidonyl-trifluoromethyl ketone (AACOCF 3 ) increases the survival of neurons and oligodendrocytes in rats that received compression spinal cord injuries (3). Moreover, it has been shown that reduced cPLA 2 ␣ expression contributes to a remarkable resistance to acute respiratory distress syndrome (ARDS), asthma, and collagen-induced arthritis in the cPLA 2 ␣-deficient mouse model (4 -6).…”
mentioning
confidence: 99%
“…Moreover, the role of cPLA 2 GIVA and sPLA 2 GIIA have not been assessed in these in vivo studies (Liu et al 2006;Titsworth et al 2007). Evidence of a detrimental role of intracellular PLA 2 s in SCI was first shown in experiments with arachidonyl trifluoromethyl ketone (AACOCF3; Huang et al 2009). AACOCF3 is a nonselective inhibitor of intracellular PLA 2 s, and in these experiments, its effects in SCI were tested over a short 7-day period after injury (Huang et al 2009).…”
Section: Pla 2 Superfamilymentioning
confidence: 99%
“…Evidence of a detrimental role of intracellular PLA 2 s in SCI was first shown in experiments with arachidonyl trifluoromethyl ketone (AACOCF3; Huang et al 2009). AACOCF3 is a nonselective inhibitor of intracellular PLA 2 s, and in these experiments, its effects in SCI were tested over a short 7-day period after injury (Huang et al 2009). This inhibitor, which blocks both cPLA 2 and iPLA 2 , led to a modest improvement in locomotor recovery and reduction of neuronal and oligodendrocyte loss (Huang et al 2009), but the relative contribution of cPLA 2 and iPLA 2 in SCI still remained to be shown.…”
Section: Pla 2 Superfamilymentioning
confidence: 99%
See 1 more Smart Citation